Edukasi Pentingnya Vaksinasi Kepada Warga Desa Sukajadi, Kabupaten Ciamis Oleh Mahasiswa Universitas Jenderal Soedirman - Krisna Mahardika (PT. Gyandharma Global Media, 2024)
Covid-19 which emerged in early 2020 has had a major impact, especially on the Indonesian people, both in terms of economic, social and health impacts. Throughout 2020 to 2021, the increase in Covid-19 in Indonesia has increased sharply. The increase in Covid-19 is due to low public awareness of prevention efforts and minimal public interest in vaccination at the beginning of the pandemic, especially the people of Sukajadi Village, Ciamis Regency. One solution that can be provided is to educate residents of Sukajadi Village, Ciamis Regency about the importance of Covid-19 vaccination and correct hoax news about vaccination. The purpose of this vaccination education activity is to increase public awareness, especially in Sukajadi Village, Ciamis, regarding Covid-19 vaccination. The method used is the Participatory Rural Appraisal method and survey. The results of this activity can increase the awareness of residents of Sukajadi Village about the importance of vaccination.